Feasibility study of reactive chromatography for the synthesis of 2-ethoxyethyl acetate using the amberlyst-15 catalyst - Gore, Jayram I.; Nadeem, Mohd; Mahajani, Sanjay M.; Mali, Nilesh A. (Industrial & Engineering Chemistry Research, 2025)
Reactive chromatography is a promising process intensification technology that combines reaction and separation in a single piece of equipment. In this study, the reaction kinetics and adsorption behavior of esterification of 2-ethoxyethanol (EC) with acetic acid (AcOH) using Amberlyst-15 as a catalyst are studied using batch reactions and reactive chromatography. Batch reactions are performed to study the kinetic behavior, and an appropriate kinetic model is proposed. To evaluate adsorption parameters, nonreactive separation experiments are performed in a fixed bed chromatographic reactor (FBCR), and results are compared with model predictions. Further, the MATLAB simulations are performed for reactive separation using kinetics and adsorption data, and results are validated by the experiments. Experimentally obtained breakthrough profiles of FBCR for reaction and desorption reveal the applicability of reactive chromatography for the synthesis of ethyl cellosolve.